An Investigation of the Use of Traditional Chinese Medicine and Complementary and Alternative Medicine in Stroke Patients. Issue 6 (November 2017) - Yeh, Mei-Ling; Chiu, Wei-Ling; Wang, Yu-Jen; Lo, Chyi
Abstract : This study aimed to investigate the use of traditional Chinese medicine and complementary and alternative medicine in stroke patients in Taiwan. Chinese herbal medicine, massage, acupuncture, natural products, and exercise were widely used among stroke patients. Integrating safe and effective traditional Chinese medicine and complementary and alternative medicine into conventional therapies is suggested.